EFFECTIVENESS OF HAIR CUT ENTREPRENEURSHIP TRAINING WITH EXPERIENTIAL LEARNING APPROACH TO IMPROVE ADOLESCENT ENTREPRENEURSHIP SKILL - Rahmadi, Andri; Ansori, Ansori (IKIP Siliwangi Bandung, 2025)
This study aims to find a training model that can improve the entrepreneurial skills of teenagers. To achieve this goal, the research developed a training model with an experiential learning approach so that after haircut entrepreneurship training, the entrepreneurial skills of teenagers can be increased. This study is a multi-disciplinary study using pre-post-test experiments without using a control group with only one type of treatment. The results of this study proved effective in improving adolescent entrepreneurial skills which include the ability to observe, experiment, communicate and make decisions and increase economic independence. so that it can be used by practitioners or organizers such as PKBM or LKP at the district/city level. The pattern of implementation with experiential learning is expected to be a complement and reinforcement in increasing youth entrepreneurial skills which are supported by policy makers in this case the Cimahi City Education Office and the Manpower Office in disseminating this model as an alternative to preparing skilled youth. there are weaknesses, shortcomings and limitations in the implementation of research so that further studies and research are needed on hair cutting entrepreneurship training with an experiential learning approach to improve the entrepreneurial skills of these teenagers.Â Â